Dimensões emancipatórias da práxis cinematográfica contra-hegemônica - Alves, Vanessa Castro (2019)
Through the historical and dialectical materialist method, the present study aims to analyze the potential of the counter-hegemonic cinematographic praxis for the development of emancipatory social processes. The research is of a qualitative nature and contemplated a theoretical-bibliographic study about the aesthetic foundations present in the Marxian work, as well as on Marxist authors who theorized about art, aesthetics and cinema. A bibliographical research was also carried out in order to know how the cinematographic praxis has been approached by the production of knowledge in the human and social sciences. At a later stage, empirical data were collected through semi-structured interviews with 11 participants working in collective and film and audiovisual projects on the margins of conventional and commercial circuits in the metropolitan region of Porto Alegre, Rio Grande do Sul. The analysis and interpretation of the data were inspired by the discursive textual analysis (MORAES; GALIAZZI, 2006). The study identified four emancipatory dimensions: memory and history dimension, political dimension, aesthetic dimension and educational dimension. These dimensions, which are constitutive of the analyzed phenomenon, are intimately interrelated and based on the following thesis: Cinema, as a phenomenon produced by capitalist society, is complex and contradictory. It is capable of manipulating consciousness, legitimizing the dominant ideology and / or revealing its contradictions, providing resources for its contestation. It carries within itself elements of domination, but also of resistance, constituting itself as object of political disputes. The dimensions of memory and history, political, aesthetic and educational, permeate the counter-hegemonic cinematic experiences investigated and constitute emancipatory social processes, insofar as they enable the decoding and exploration of the world, promoting critical thinking, free creation, autonomy and the construction of political subjects, essential elements to contribute to human emancipation. However, the contribution of the cinematographic praxis to the ideological dispute takes place in the articulation with the social struggles in political practice, because in isolation it does not have concrete mechanisms capable of promoting a radical structural change or a retreat from the dominant thought. The cinematographic art is conditioned by subjective characteristics and by the vision of the world of its directors, reflecting still, the socio-historical determinations of a certain time in which it was produced. It has, however, relative autonomy, allowing moments of freedom that go beyond its social conditioning, and can not therefore be reduced to its ideological dimension, nor to any utilitarian function, since above all, it is the fruit of the essential creative dimension of the human being. Although it fulfills several functions - ideological, political, cognitive, educational and aesthetic, cinema, as a human creation, satisfies the need for human beings to express themselves in a concrete sensitive object, but also in fruition, especially in view of their need for humanization.